Auditory Memory Training in Children with Learning Disability - Theaja Kuriakose; Bhavya Mahadevaiah; Nagashreeya Dinesh (Journal of All India Institute of Speech and Hearing, 1970)
Children with Learning Disability (LD) often have impairments in work- ing memory, which may contribute to de ciencies in other cognitive areas. An increased awareness of the negative consequences of working memory diculties among educational and health practitioners has augmented demand for targeted interventions over recent years. The present study attempted to investigate the eectiveness of auditory memory training on auditory memory in children with LD. Two groups in the age range of 6 to 8 years served as of participants in the present study. Group I consisted of 16 normal children and group II consisted of 10 children studying in the academic grades 1st to 3rd diagnosed as having LD. The study was carried out in three dierent phases. In phase one pre- therapyauditory memory testing while in phase two auditory memory training and phase three had therapy auditory memory testing. The two groups were compared using independent sample t-test and the results indicated a signi cant dierence in performance in auditory memory tasks between the two groups before the training programme. However, after the training programme there was no statistically signi cant dierence between normal children and children with LD. The results of the present study indicate that intensive training improves the auditory memory of children with LD.